Analisis permintaan konsumen terhadap minyak goreng di Kota Dumai - Rosalina, Sondang; Hamidi, Wahyu; ', Jahrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in the city of Dumai. The purpose of this study was to determine the factors that influence consumer demand for edible oil in Dumai. The data used in this study are secondary data and primary data with the data analisisis method is descriptive quantitative and qualitative analysis. As for the population in this research is that households residing in the city of Dumai by taking two districts in the city dumai where the number of samples taken was 100 respondents using Slovin formula. From the research that has been conducted, the simultaneous regression test (F test) showed that income, household size, and price simultaneously significant effect on the demand for edible oil in Dumai. Partial regression test (t test) showed that the investment variables have the most significant effect on the demand for edible oil in Dumai is income. The magnitude of the effect that (R2) of 0.286 whice means that consumer demand for edible oils as the dependent variable able to be explained by the independent variables are income, number of household members, and the price was 28.6% and the rest is explained by variables - variables others outside the model.Keywords: Demand, income, population, and price